STRATEGI KOMUNIKASI D’KANDANG AMAZING FARM DALAM MEMPERTAHANKAN NILAI REVISIT INTENTION WISATAWAN - Mutiara Maharani, Maylani; Ghozali Moenawar, Mohamad; Dharmawan, Leonard; Manisya, Nabhila; Azzahra, Maharani (Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, 2025)
This study explores communication strategies in the tourism sector, with the primary objective of analyzing the communication strategies implemented by D’Kandang Amazing Farm to enhance tourists' revisit intention. The research employs a qualitative method, involving data collection through interviews with three key informants. This study adopts the Integrated Marketing Communication (IMC) theory approach. The implementation of the IMC theory approach, which aligns with D’Kandang Amazing Farm’s communication strategy, includes personal selling, sales promotion, digital marketing, and events. The findings indicate that D’Kandang Amazing Farm’s strategy is predominantly evaluated through direct customer surveys. The survey results are collected and discussed in a weekly evaluation meeting involving all management members. The evaluation outcomes serve as the basis for improvements that are expected to align with visitors' preferences. Additionally, the communication strategy also involves utilizing social media platforms such as Instagram and TikTok to disseminate information and updates about D’Kandang Amazing Farm to visitors. Moreover, the farm organizes festivals and events to attract a larger audience. The implementation of these communication strategies has successfully increased revisit intention and continues to show growth.